ANALISIS KEBIJAKAN PEMERINTAH PROVINSI JAWA BARAT DALAM PENANGANAN COVID `19 (Institut Pemerintahan Dalam Negeri, 2020)
Covid Handling Policy 19 in West Java Province, the Governor of West Java in the implementation of its handling always refers to what is the policy of the central government, the policy of budget recorfusing carried out by the government towards the 2020 state budget, the provincial government also recofuses the provincial and regency / regional budgets City, so that the policies undertaken to overcome the response of Covid 19 always rests on policies made by the central government. Because of the 19th Impact in Indonesia, it has been very serious and has spread in 34 provinces in Indonesia, and nearly 400 districts / cities in Indonesia. The policy of implementing phase 1 PSBB in Depok, Bogor and Bekasi, is an early stage PSBB, because in that area, is a buffer for the Capital City area of DKI Jakarta, where DKI Jakarta is the highest pendemic cluster in Indonesia, and most of the people of West Java, earn a living in Capital of DKI Jakarta. Relocating a budget for handling Covid 19 in West Java is budgeted to reach almost 8 trillion, and added budget relocation in several regencies / cities in West Java, to cope with handling Covid 19, is the seriousness of the local government in handling the Covid 19 problem in West Java. For this reason, researchers are interested in conducting research with the title “Policy Analysis of the Government of West Java Province in handling Covid 19” This study uses descriptive qualitative methods, by studying and analyzing and describing secondary data obtained by researchers and the results achieved are the Implementation of Government Policy West Java Province in handling Covid 19, went very well, and originally West Java was included in a group of 4 (four) major, now getting better and entering the ranks of the top 10 spread of Covid 19 in Indonesia, and some areas have entered the yellow zone and green zone , as well as the blue zone (this paper was released in early July 2020).Keywords: Policy analysis, Government, West Java, Covid 19